Kitchen privileges : a memoir - Clark, Mary Higgins (New York Simon & Schuster, 2002)
In a charming, bittersweet memoir of growing up in the Bronx during the Depression, America's Queen of Suspense shares her recollections of her father's death in 1939, her family's financial woes, and her mother's creation of a rooming house, bringing in a colorful assortment of tenants who will change the lives of the Higgins clan.
D., A Morrow, 2/28/2006
Keywords: Clark, Mary Higgins -- Biography